Validation of the Singapore nomogram for outcome prediction in breast phyllodes tumours in a large patient cohort. Issue 2 (27th July 2017) - Chng, Tze Wei; Gudi, Mihir; Lim, Swee Ho; Li, HuiHua; Tan, Puay Hoon
Abstract : Aims: To validate the Singapore nomogram for outcome prediction in breast phyllodes tumours in a large cohort of Singaporean patients, as previous validation studies were conducted on small numbers of patients. We also investigate the association of fibroadenomas and phyllodes tumours within a subset of our cohort. Methods: Histological parameters, surgical margin status and clinical follow-up data of 259 women diagnosed with phyllodes tumours were analysed. Patients with concurrent malignant or premalignant disease were excluded from the validation to minimise confounding influences. Biostatistics modelling was performed, and the concordance between predicted and observed survivals was calculated. The association between fibroadenomas and phyllodes tumours was quantified in a subset of the women. Results: Phyllodes tumours with higher number of mitoses, stromal overgrowth and positive surgical margins were found to be associated with greater risk of clinical recurrence. Patients with a higher nomogram score had a significantly higher risk of developing relapse. Forty out of 78 (51.3%) of the subset of phyllodes cases reviewed showed either fibroadenoma-like areas within the phyllodes tumours or concurrent fibroadenomas in the ipsilateral or contralateral breast. Conclusions: The Singapore nomogram is useful in predicting outcome in breast phyllodes tumours when applied to a large cohort of Singaporean women.